Minimum Wage and Its Impact on the Job Market in Germany - Nyklewicz, Krzysztof (Olsztyn Economic Journal, 2016)
The introduction of the national minimum wage in Germany in 2015 is an important yet controversial instrument of labour market policy. This paper represents an attempt to define the scope of influence it has on companies and employees in respective branches of economy (accommodation and food services business, retail trade, manufacture of food products, transportation and warehouse management). In order to accomplish it the method of analysis and criticism of literature has been applied. It allowed to conduct an evaluation of the discussed dependence.The preliminary findings indicate that interference is especially high in the low wages sector. To show the consequences the national minimum wage has on the job market, positive changes in employment and unemployment levels in the given period (the increase in the first and the drop in the second one) were presented. This meant that the fears concerning a few thousand job losses, as a result of introducing the minimum wage, were unjustified. In this paper articles and analyses published by German research institutes were used. The statistical data comes from the databases of these institutes and of the Federal Employment Agency. The research period considers the years 2014-2015, specifically one year before and half a year after the introduction of the minimum wage in Germany with the aim of highlighting the changes in the employment size caused by the minimum wage.